Independent Ruler, Indefinable Role - Yihao QIU (Revue des Mondes Musulmans et de la Méditerranée)
Abstract: This study discusses the history of the Golden Horde and the political status of the Jochid ulus from the perspective of the Yuan Dynasty. According to traditional narratives, the rulers of the Jochid ulus were largely antagonistic and apathetic towards the Yuan Court. However, Chinese sources present a somewhat different picture and shed new light on several issues, including the status of Jochid rulers in the eyes of Yuan historians, the importance of Jochid apanages in China, local dual-administrative structures, and local officials of the Great Khan. The importance of Berke’s conversion to Islam and how this influenced the conflict between the Jochids and Toluids is also touched upon. The contribution ends with a discussion of the relationship between the Golden Horde and the Yuan Dynasty in the post-Berke period.